Determination of diferences in runs between boys and girls aged 5.5 Určení rozdílu v běhu mezi chlapci a dívkami ve věku 5,5 roku - Damir Karpljuk; Jože Štihec; Mateja Videmšek (Palacky University, 2005)
The aim of this research is to determine whether there are distinctions in runs among five and a half year old boys and girls. The research is based on studying 80 girls and 64 boys from seven kindergartens in Slovenia. The following five measurement methods have been used in our research: a 10-meter run, a 150-meter run, a 10-meter run with a flying start, 4-times 5-meter run, and a 300-meter run. The results of the t-test indicate a statistically characteristic difference among boys and girls in 300 m run test results only, that is, a method used for measuring aerobic endurance. Other motor skills results have shown that there are no statistically characteristic differences among boys and girls. It is important that sport activities for boys and girls are organized for both groups of children equally. Especially girls must take part in a variety of running exercises in order to increase their aerobic endurance. They should be encouraged to take part in a variety of games which require activating the energy component of movement. Based on the results of this research we can say that physical education (PE) of preschool children should be planned regardless of sex and the PE program should be the same for both boys and girls. Cílem tohoto výzkumu je určit, zda existují odlišnosti v běhu chlapců a dívek ve věku 5,5 roku. Výzkum je založen na studii 80 dívek a 64 chlapců v sedmi mateřských školách ve Slovinsku. Bylo použito těchto pěti měřicích metod: běh na 10 metrů, běh na 150 metrů, běh na 10 metrů s letmým startem, běh 4 × 5 metrů, běh na 300 metrů. Výsledky t-testu vykázaly statisticky významný rozdíl mezi chlapci a dívkami jen v běhu na 300 metrů, což je metoda používaná pro měření aerobní vytrvalosti. Výsledky ostatních pohybových aktivit vykazují, že mezi chlapci a dívkami není žádný statisticky významný rozdíl. Je důležité, aby sportovní aktivity byly organizovány rovnoměrně jak pro chlapce, tak pro dívky. Obzvláště děvčata se musí účastnit různých běžeckých cvičení v zájmu toho, aby vzrostla jejich aerobní vytrvalost. Měla by být povzbuzována, aby se účastnila různých her, které vyžadují aktivaci energetické složky pohybu. Na základě výsledků tohoto výzkumu můžeme říci, že tělesná výchova (TV) předškolních dětí by měla být plánována bez ohledu na pohlaví a že tělovýchovný program by měl být pro chlapce i dívky stejný.